The Role of PCR in Diagnosis of a Rare Appendicular Tuberculosis and Mini Literature Review - Asmerom Tesfamariam Sengal; Ahmed Abdalla Mohamedani; Hanan Hasaan Hussein; Alaa Kamal (Case Reports in Gastrointestinal Medicine)
Tuberculosis is a prevalent public health problem especially in the poor developing countries and results in significant mortality. Albeit tuberculosis almost always affects any organ or system of the body, abdominal tuberculosis is less frequent; moreover, tuberculous appendicitis is very rare with an incidence estimated at about 0.1–0.6% of all gastrointestinal tuberculosis. The purpose of this report was to present an unusual case of primary tuberculous appendicitis and the approach used for accurate diagnosis as well as a current update on the disease. We are reporting a 30-year-old male who presented with acute abdominal pain, fever, and vomiting and was admitted with the clinical diagnosis of acute appendicitis. Patient was investigated thoroughly and histopathologic examination was strongly suggestive of tuberculous appendicitis; however, Ziehl-Neelsen (ZN) was negative in tissue section. To confirm the diagnosis, molecular biology [polymerase chain reaction (PCR)] study was performed from the formalin fixed paraffin embedded (FFPE) appendicular tissue and revealed presence of Mycobacterium tuberculosis. As there are numerous differential diagnoses in granulomatous lesions of appendix and due to the fact that appendicular tuberculosis is a rare phenomenon; verification etiologic agent is crucial for appropriate management of the disease.